STUDENTS' ENGLISH VOWEL PRONUNCIATION IN HANDLING PHONE CALLS - Paramita Sari, Ni Luh Komang Julyanti; Saharjo, Sulistyo Joko; Prayogi, Putu Agus (Jurnal Manajemen Pelayanan Hotel, 2022)
Language is an important aspect of communication, and is a tool for expressing ourself, thoughts and ideas. Currently, people are required to master a foreign language, one of the most widely used languages is English. In mastering English, as well as learning languages in general, it has been divided into five skills, namely speaking, listening, writing, reading, and structure/ grammar. One of the skills discussed in this study is speaking (pronunciation of vowels) in the practice of handling telephone calls. In this study, data collection was collected by using the observation method and the data analyzed in this study were qualitative data. The data was obtained from 20 students of Triatma Mulya University who were taking English course in Post Intermediate Level. Then the data was processed using qualitative descriptive analysis techniques. During the learning process, students experience problems in pronouncing English. This can be seen in the pronunciation of vowel sounds that are not in accordance with the pronunciation standards in English especially vowel pronunciation such as /É”/ which becomes /a/, vowel /É’/ which becomes /o/, /i:/ which becomes /e/, and vowel /u:/ which becomes /o/. In addition to students' English pronunciation, during the learning process several obstacles were also found, such as barriers from linguistic factors, barriers to mastery of content components including topics, content structure, content quality, and content quantity. Keywords: speaking, pronunciation, vowel sounds.